Meretas Involusi Kajian Hukum Islam di Indonesia: Pengalaman Fakultas Syariah dan Hukum UIN Sunan Kalijaga Yogyakarta - Noorhaidi Hasan (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2012)
The study of Islamic law requires a shifting paradigm from text to context and demands an inter-disciplinary approach involving various disciplines in social sciences. A text-based legal-normative approach is no longer adequate to ensure the relevance of the study of Islamic law with the current changes as a result of modernization and globalization. Perspectives of social sciences provides not only the lens to see Islamic law as a fact social, but also offers the analitical frameworks to explain how Islamic law engages with the context and receives new meanings and interpretations in its complex interaction with other forms of social practices. In tandem with growing awareness among Muslim intellectuals of the importance of actualizing Islamic law with the spirit of changes, the studies and researches at the Faculty of Sharia and Law at Sunan Kalijaga State Islamic University of Yogyakarta have thrived by utilizing and integrating social sciences into their paradigm, method and analytical construct. Within this context the so-called "mazhab Yogya? came into being. This new trend of thought pays a special attention to the effort of reactualizing fiqh as knowledge about the basic principles used as a reference in formulating Islamic law in accordance with local context.